2022
DOI: 10.1002/ppul.26053
|View full text |Cite
|
Sign up to set email alerts
|

How did respiratory syncytial virus and other pediatric respiratory viruses change during the COVID‐19 pandemic?

Abstract: The seasonal cycle of pediatric respiratory viral illnesses in temperate regions, like the U.S., occurs in a similar pattern every year This article is protected by copyright. All rights reserved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 8 publications
0
8
0
Order By: Relevance
“…14 A retrospective review in the USA showed only 1.4% of cases were infected with SARS-CoV-2 and RSV simultaneously in 2021. 88 In Italy, the co-infection rate of SARS-CoV-2 and other respiratory viruses was around 7.6% in all positive samples. None of these cases showed co-infection with SARS-CoV-2 and RSV.…”
Section: Sars-cov-2 Co-infection With Respiratory Syncytial Virusmentioning
confidence: 93%
“…14 A retrospective review in the USA showed only 1.4% of cases were infected with SARS-CoV-2 and RSV simultaneously in 2021. 88 In Italy, the co-infection rate of SARS-CoV-2 and other respiratory viruses was around 7.6% in all positive samples. None of these cases showed co-infection with SARS-CoV-2 and RSV.…”
Section: Sars-cov-2 Co-infection With Respiratory Syncytial Virusmentioning
confidence: 93%
“…Among hospitalized children, we report 7% RSV‐positive cases with co‐infections of RSV and SARS‐CoV‐2, while only a single case (0.9%) was detected with both RSV and influenza. According to a retrospective review study in United States 2021, only 1.4% were co‐infected with RSV and SARS‐CoV‐2, 31 while in UK, between February 2020 and December 2021, 3.2% were co‐infected with RSV and SARS‐CoV‐2 32 . Studies from Italy, Poland, and South Africa did not report such co‐infections, 33–35 however, in Iran and Brazil they found high rates of co‐infections with SARS‐CoV‐2 and influenza, ranging from 9.7% to 22.3% 36,37 .…”
Section: Discussionmentioning
confidence: 99%
“…20 We suggest several explanations for our findings: (1) the enforced social distancing and restrictions measures were associated with a lower rate of respiratory viral diseases, representing true lower AOM rates during the COVID years. Several reports support this theory by reporting on a significant reduction in isolations of human metapneumovirus, parainfluenza, rhinovirus, respiratory syncytial virus, and influenza virus during the first COVID year [21][22][23] ; (2) The fluctuations in AOM burden during the COVID years coincided with the alternating lockdown/relaxation periods in Israel. The "seasonal switch" observed during the first two COVID years, with higher AOM incidence rates during the summer and lower incidence rates during the winter, can be attributed to the major lockdowns and educational institutions closure during the winter months in both COVID years.…”
Section: Discussionmentioning
confidence: 99%